Benefit from Income Diversification of Viet Nam Commercial Banks - Nguyen, Dinh; Phi Hong, Hanh (VNU Journal of Science: Policy and Management Studies, 2017)
In this study, relationship between non-interest income generating activities (income diversification) and bank performance is investigated by using an unbalanced panel dataset of ten commercial banks listed on Vietnam stock market during the period 2007–2016. Our empirical results indicate that income diversification decrease insolvency risk and enhance performance of listed banks and the relationship between income diversification and bank performance is non-linear. In addition to be affected by factors of income diversification, bank performance is also affected by banks ’ characteristics and business environment factors. Bank size, deposit on total liabilities ratio, the first lags risk adjusted returns have positive effects on bank performance while the effect of enforcement index on bank performance is negative. Keywords : Income diversification, bank performance, banks